DEVELOPMENT A DAILY NUTRITIONAL ADEQUACY BALANCE IDENTIFICATION SYSTEM AS AN EFFORT TO PREVENT MALNUTRITION (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2024)
Malnutrition is a deficiency, excess or imbalance in a person's energy and nutritional intake. Malnutrition can occur when a person has too much or too little food and important nutrients in their body. The Ministry of Health, Indonesia, has campaigned for food consumption that complies with balanced nutrition guidelines under the slogan "Isi Piringku". However, the guidelines regarding this matter are still not properly understood by the public. Even if implemented, the nutritional levels contained in one portion of food consumed cannot yet be measured. Thus,  to identify the fulfillment of balanced nutritional, a device is needed to easily detect how much calories is consumed. Therefore, this research aims to develop a system which can identify whether the portion of food consumed meets balanced nutrition or not. It is developed in Django framework, Python programming language, and MySQL database. It has been evaluated using black box testing, white box testing, and system usability scales. The result shows that all system requirements have been run well. Meanwhile, system usability testing result shows that the identification system has been tested with a score of 82 and categorized in Excellent.
Keywords: Identification; nutritional adequacy; nutritional balance; software development